Presence of high grade tertiary Gleason pattern upgrades the Gleason sum score and is inversely associated with biochemical recurrence-free survival - BOZKURT, SÜHEYLA (ELSEVIER SCIENCE INC, 2013)
Objectives: Tumor heterogeneity is a common finding and led to realization of a tertiary Gleason component (TGC) in prostate cancer. In an attempt to further investigate its prognostic value, we analyzed the association of tertiary Gleason pattern in Gleason score <= 7 tumors with pathologic stage and biochemical disease-free survival. Material and methods: A total of 331 radical prostatectomy specimens were analyzed retrospectively. The primary, secondary, and the tertiary patterns were evaluated by reviewing all of the pathologic slides. TGC was defined as Gleason grade pattern 4 or 5 for Gleason score <7 tumors and Gleason grade pattern 5 for Gleason score 7 tumors. The pathologic prognostic factors, (extraprostatic extension, seminal vesicle and lymph node invasion, surgical margin status) of Gleason score <7, 3+4, and 4+3 tumors with or without TGC were compared. Biochemical recurrence-free survival (BRFS) was calculated using Kaplan-Meier method with log rank test, and the influence of TGC was assessed in a Cox regression model. Results: TGC observed more frequently with higher Gleason scores (21% of the GS <7 cases, 23% of the GS 3+4 cases, and 58% of the GS 4+3 cases). In terms of adverse pathologic prognostic factors and BRFS, GS <7 tumors with TGC behaved significantly worse than GS <7 tumors without TGC (P = 0.01 and P = 0.001, respectively) with properties similar to GS 3+4 tumors without TGC. Gleason score 3+4 and 4+3 tumors without TGC were statistically similar and had better features than corresponding tumors of same Gleason score with TGC. Furthermore, Gleason score 7 tumors with TGC had similar features with GS 8-10 tumors. During follow-up, 73 (22%) subjects had PSA recurrence. In the Cox regression model TGC was an independent variable for BRFS (BR = 2.63, 95% CI = 1.39-4.98, P = 0.003). Conclusion: According to the present study, 3 different prognostic groups were observed; good prognostic group: GS <7, intermediate prognostic group: GS <7+TGC, GS 3+4, and GS 4+3, and finally bad prognostic group: GS (3+4)+TGC, GS (4+3)+TGC, GS >7. Presence of a TGC appears to upgrade the total score and adjuvant treatment decisions may further be refined by considering the tertiary pattern. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Prostate cancer pathology; Tertiary Gleason; Survival; RADICAL PROSTATECTOMY SPECIMENS; PROGNOSTIC-SIGNIFICANCE; PROSTATIC ADENOCARCINOMA; MULTIVARIATE-ANALYSIS; PATHOLOGICAL STAGE; CANCER; PROGRESSION; PREDICTION; CARCINOMA; MEN